ECAS : English communication arts and skills through Anglo-American and Philippine literatures 9 - Serrano, Josephine B.; Lapid, Milagros G. (Quezon City : Phoenix Publishing House, Inc., 2018)
"The 8th edition of ECAS promises a framework and discussions that address contemporary and current issues and concerns germane to language, cultures, identities, and texts, with Philippine literature as the framing lens. While it continues to bring in the classics, the vision and perspective of the Series have taken some readjustments, tackling the materials with a certain "edge" and purposiveness, and with an essentially 21st century stance, out-look, and projected outcome."
English text.
Keywords: Literature -- Study and teaching